ANALISIS PERBANDINGAN KELAYAKAN INVESTASI PROPERTI APARTEMEN DENGAN HOUSE LANDED JAKARTA GARDEN CITY (JGC) - Soesanto, Handjoyo; Dermawan, Hans (Jurnal Aplikasi Teknik Sipil, 2024)
Cakung with an area of 42,278 Km2, will be carrying out a regional development process which is supported by one of the developers PT. Modernland Realty Tbk in the residential area of Jakarta Garden City. This research is focused on the comparison of the feasibility value of apartment investment with house landed for potential investors. The research data is processed through a comparison of investment feasibility value analysis using the calculation method of NPV (Net Present Value), IRR (Internal Rate of Return), BCR (Benefit Cost Ratio), and Sensitivity Analysis within the next 30 years with an interest rate of 3,47% and 4,25%. The results of a comparative analysis of the feasibility of property investment at an interest percentage of 3.47% for an apartment's NPV value of Rp. 2,374,811,235 and a house's NPV value of Rp. 353,721,256. The IRR value for apartments is 7.7% and for houses is 4.8%. The BCR value for apartments is 2.18 > 1 and for houses is 2.08 > 1. Sensitivity analysis on the NPV value of apartments with a return value of 7.7% (Rp. 630,183,652 > 0) and NPV of a house with a return value of 4.8% (Rp. 680 .005 > 0). The results of the research will be information or material for consideration, especially for potential investors in choosing a form of property investment.